Successfully reported this slideshow.
We use your LinkedIn profile and activity data to personalize ads and to show you more relevant ads. You can change your ad preferences anytime.

Factorising quadratic expressions 1

735 views

Published on

Factorising quadratic expressions by inspsection with quadratic coefficient equal to 1

Published in: Technology, Business
  • Be the first to comment

  • Be the first to like this

Factorising quadratic expressions 1

  1. 1. Factorise the following expressions: 6 y2   ­  5y = 9  a3    ­  3 a2       = x2   +  xy  +  3 x z = x2    +   5 x   + 6 =
  2. 2. x2    +   5 x   + 6   This expression is  called a  quadratic expression  because the highest power of any of its terms is  2.  
  3. 3. Factorising quadratic expressions By the end of the lesson you will be able to: • Factorise quadratic expressions of the form        x2  + bx  + c .
  4. 4. Expand and simplify the following: (x+2) ( x+3) = (x+4) ( x ­5) = (x ­ 6) ( x+3) = (x+5) ( x ­ 2) = (x ­ 5) ( x ­ 3) = (x+4) ( x+5) = Do you observe any pattern?
  5. 5. Expand and simplify the following:  (x+2) ( x+3) =   x2  + 5 x + 6 (x+4) ( x ­5) =    x2  ­  x ­  20 (x ­ 6) ( x+3) =    x2  ­ 3 x ­ 18 (x+5) ( x ­ 2) =   x2  + 3 x ­ 10 (x ­ 5) ( x ­ 3) =    x2  ­ 8 x  + 15 (x+4) ( x+5) =    x2  + 9 x + 20 Do you observe any pattern?
  6. 6. (x+2) ( x+3) =  x2     +    5  x    +6   (x+4) ( x+5) =  x2  +   9  x   + 20 (x ­ 6) ( x+3) = x2    ­ 3  x   ­ 18
  7. 7. (x+2) ( x+3) =  x2     +    5  x    +6  2 x 3   2 + 3 4 x 5 (x+4) ( x+5) =  x2  +   9  x   + 20 4+ 5 (x ­ 6) ( x+3) = x2    ­ 3  x   ­ 18 ­6  x 3­6+ 3
  8. 8. (x + 4) ( x ­ 5) =  x2     ­       x    ­ 20 (x+5) ( x ­2) =    x2   +    3  x    ­ 10 (x ­ 5) ( x ­ 3) = x2    ­ 8  x   + 15
  9. 9. ( x + 3 ) ( x + 2 )           =            x2  + 5 x  + 6 Expand Factorise
  10. 10.   Therefore,   (x +2 ) ( x + 3)  x2   +   5 x  + 6   = product :  6 sum: 5 x2   +  7 x  +  12  =   (  x         )  (   x           ) product : 12 sum: 7 x2   +  4x   ­  12  =   (  x         )  (   x           ) product : ­12 sum: 4 two numbers such that: two numbers such that:
  11. 11. x2   ­  6x   +  8  =   (             )  (               ) product :   sum:   x2   + 8 x   + 15  =   (           )  (              ) product :   sum:   x2   ­  12 x   + 20 =   (           )  (               ) product :   sum:   x2   ­  9 x   ­ 36 =   (           )  (               ) product :   sum:  
  12. 12. Solve worksheet "Factorisation of quadratics "  Extra­practice:  Book Ex. 6.10  :  1 to 5
  13. 13. http://www.maths­bingo.com/FactoringQuadraticTrinomials.html
  14. 14. worksheets to print
  15. 15. Expand and simplify the following: (x+2) ( x+3) = (x+4) ( x ­5) = (x ­ 6) ( x+3) = (x+5) ( x ­ 2) = (x ­ 5) ( x ­ 3) = (x+4) ( x+5) = Do you observe any pattern?
  16. 16. (x+2) ( x+3) =  x2     +    5  x    +6   (x+4) ( x+5) =  x2  +   9  x   + 20 (x ­ 6) ( x+3) = x2    ­ 3  x   ­ 18
  17. 17. (x + 4) ( x ­ 5) =  x2     ­       x    ­ 20 (x+5) ( x ­2) =    x2   +    3  x    ­ 10 (x ­ 5) ( x ­ 3) = x2    ­ 8  x   + 15
  18. 18.  Therefore,   (x +2 ) ( x + 3)  x2   +   5 x  + 6   = product :  6 sum: 5 x2   +  7 x  +  12  =   (  x         )  (   x           ) product : 12 sum: 7 x2   +  4x   ­  12  =   (  x         )  (   x           ) product : ­12 sum: 4 two numbers such that: two numbers such that:
  19. 19. x2   ­  6x   +  8  =   (            )  (               ) product :   sum:   x2   + 8 x   + 15  =   (           )  (               ) product :   sum:   x2   ­  12 x   + 20 =   (            )  (               ) product :   sum:   x2   ­  9 x   ­ 36 =   (            )  (   x           ) product :   sum:  

×